Making Sense? The structure and meaning of digital memetic nonsense - Katz, Yuval; Shifman, Limor (AoIR Selected Papers of Internet Research, 2016)
This paper offers a first systematic analysis of “digital memetic nonsense.” While memetic nonsense is a new, understudied phenomenon, nonsensical utterances have been part of human culture for centuries and have received considerable scholarly attention, resulting in three main perspectives on nonsense: nonsense as lack of meaning, nonsense as play with meaning and nonsense as deconstruction of meaning. When re-examining these classic definitions in digital contexts, we highlight the relevance of three features of such environments to the augmented formation of nonsense: phatic communities, visual dominance and remix culture. Our examination focuses on nonsensical memes – clusters of digital texts imitated and circulated by many participants. A grounded and multimodal analysis of 154 nonsensical memes led to the identification of five distinct types of digital memetic nonsense: linguistic silliness, embodied silliness, pastiche, dislocations and interruptions. An integrated evaluation of these categories revealed that digital forms of nonsense mark a major shift from pre-digital ones. While the latter often deconstruct meaning as a subversive ideological act, the former lean more heavily towards mere playfulness. This playfulness has nonetheless important social roles. It replaces the intellectual approach, seeking to deconstruct or defy meaning, with a more communicative/communitive approach, emphasizing that meaning is flexible and can be negotiated between members of meme-based communities. Thus, while nonsensical memes often lack referential meaning, they always carry a social meaning. Moreover, this obliteration of meaning may enable the creation of inclusive communities, in which a variety of participants are invited to express their quirky creatively.